Coordinated robust control of DFIG wind turbine and pss for stabilization of power oscillations considering system uncertainties - Surinkaew, Tossaporn; Ngamroo, Issarachai (My University, 2014)
Uncertainties in power systems, such as intermittent wind power, generating and loading conditions may cause the malfunction of power system stabilizing controllers, which are designed without considering such uncertainties. To enhance the robustness of stabilizing controllers against system uncertainties, this paper proposes a new coordinated robust control of doubly fed induction generator (DFIG) wind turbine equipped with power oscillation damper (POD) and synchronous generator installed with power system stabilizer (PSS) for stabilization of power system oscillations. Without the difficulty of mathematical representation, the inverse output multiplicative perturbation is used to model system uncertainties. The structure of POD and PSS is specified as a practical second-order lead/lag compensator with single input. The parameters optimization of POD and PSS is conducted so that the stabilizing performance and robustness of POD and PSS are augmented. The improved firefly algorithm is applied to solve the optimization problem and achieve the POD and PSS parameters automatically. Simulation study in the modified IEEE-39 bus New England system included with DFIG wind turbines ensures that the robustness and stabilizing performance of the proposed coordinated DFIG with POD and PSS are much superior to those of the conventional DFIG with POD and PSS under various severe disturbances and system uncertainties. © 2014 IEEE.
Keywords: Doubly fed induction generator (DFIG) wind turbine; firefly algorithm; power system oscillation; power system stabilizer (PSS); robust control; system uncertainties